A preliminary study of the psychological differences in infertile couples and their relation to the coping styles - Musa, Ramli; Ramli, Roszaman; Abdul Wahab, Azantee Yazmie; Mohd Bustaman, Siti Khadijah; Mohd Yatim, Hayati; Midin, Marhani; Nik Jaafar, Nik Ruzyanei; Das, Srijit; Sidi, Hatta; Ravindran, Arun (Elsevier, 2014)
Background: Studies from Western countries have observed that couples undergoing infertility treatment suffer various physical and psychological difficulties at a higher frequency than the comparable general population. These relate to treatment challenges and other psychosocial stressors, often influenced by coping style, personality factors and available support systems. There is paucity of studies in non-Western populations.